A Clinical Study Comparing the Efficacy of SesameOil with Desensitizing Tooth Paste in Reducing Dentinal Hypersensitivity: A Randomized Controlled Trial. (9th October 2020) - Abdullah Al Qahtani, Walaa; Sandeepa, N. C.; Khalid Abdullah, Eman; Mohammed Mousa, Yosra; Abdulhade Ganem, Atheer; Ali Alqahtani, Eman; Alkhayri, Afnan Hassan M.
Abstract : Context . Several treatments are available for management of dentinal hypersensitivity, most routinely recommended one being desensitizing tooth paste with variable results. This is a clinical trial to study the therapeutic effectiveness of sesame oil which is an essential oil, a commonly available household traditional medicine with several health benefits. Objectives . The objective of this study was to evaluate the efficacy of sesame oil therapy in reduction of dentin hypersensitivity, as compared to desensitizing dentifrice. Design, setting, participants . We conducted a single blinded randomized controlled trial in 100 patients reported to Diagnostic Department of King Khalid University-College of Dentistry between March 2018 and December 2019. Interventions . Patients were given desensitizing tooth paste or sesame oil to apply for the specified time. Main outcome measures . A Visual Analogue Scale was used to record sensitivity scores for controlled air stimulus and tactile method at the first visit and after 8th week of treatment. Measured outcome was reduction in dentinal hypersensitivity. Results . Hypersensitivity degree before treatment in case of desensitizing tooth paste was 6.90 ± 1.04, and posttreatment showed a score of 4.70 ± 1.37. In case of sesame oil groups, subjects included had a score of 7.14 ± 0.90 which showed a drop to a score of 4.52 ± 1.16. Conclusions . Desensitizing tooth paste showed 30.5% reduction in sensitivity, whereas sesame oil application showed 36.2% reduction. The belief of considering oil therapy in oral health is just a placebo effect and may not be considered anymore. Efficacy can be established with many more studies including long follow-up and varying time periods.